Ocean defenders and human rights - Bennett, Nathan J.; López de la Lama, Rocío; Le Billon, Philippe; Ertör, Irmak; Morgera, Elisa (Frontiers in Marine Science, 2023)
Two pressing and overlapping marine policy issues are related to human rights in the ocean and the situation of ocean defenders. Human rights issues and violations are on the rise in the ocean due to the ongoing, rapid and unchecked escalation of anthropogenic activities in marine and coastal environments, which increasingly undermine the fundamental, civil and political, economic, social, cultural or environmental rights of individuals and groups. In this context, it is essential to recognize, support and safeguard the individuals, groups or communities who are mobilizing, advocating or taking action to protect the marine environment, coastal and oceanic territories, and associated human rights from existential threats. Yet, these ‘ocean defenders’ often face marginalization, intimidation, criminalization, threats, violence and murders. The failure to protect the human rights of coastal populations and ocean defenders needs to be urgently rectified by states, the private sector and civil society. We identify six specific areas of urgent action to confront human rights issues in the ocean and to support and safeguard ocean defenders.